2007
DOI: 10.1158/0008-5472.can-06-2112
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tumor-Associated Differentiation Antigens, MUC1 Glycoforms and CEA, in Human Thymic Epithelial Cells: Implications for Self-Tolerance and Tumor Therapy

Abstract: Expression of tissue-restricted self-antigens in the thymus, termed promiscuous gene expression, imposes T cell tolerance and protects from autoimmune diseases. This antigen pool also includes various types of tumor-associated antigens (TAA) previously thought to be secluded from the immune system. The scope of promiscuous gene expression has been defined by mRNA analysis at the global level of isolated medullary thymic epithelial cells (mTECs). Information at the protein level on the frequency of mTECs expres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 44 publications
4
50
1
1
Order By: Relevance
“…Therefore, thymus-re-entering T cells could also play beneficial roles in therapies, such as the highly successful adoptive transfer of tumor-specific T cells in immunedepleted cancer patients (53); tumor-specific T cells are adoptively transferred into lymphopenic cancer patients, where they expand, gain effector functions, and are able to remove tumor cells with high efficiency (53). Because thymic DCs and mTECs present tumor (self-)Ags (54,55), their possible removal might positively enhance the endogenous antitumor repertoire of the patients, similar to the appearance of OVA-specific T cells in our mouse model system (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, thymus-re-entering T cells could also play beneficial roles in therapies, such as the highly successful adoptive transfer of tumor-specific T cells in immunedepleted cancer patients (53); tumor-specific T cells are adoptively transferred into lymphopenic cancer patients, where they expand, gain effector functions, and are able to remove tumor cells with high efficiency (53). Because thymic DCs and mTECs present tumor (self-)Ags (54,55), their possible removal might positively enhance the endogenous antitumor repertoire of the patients, similar to the appearance of OVA-specific T cells in our mouse model system (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…The first one suggests that immune rejection of the tumor does not occur due to fact the tumor is recognized as immunologically normal tissue. Tumor cells express tumor-associated antigens (TAA), which can be normally present on host cells, so induction of an effective anti-tumor immune response is not achieved [120,121]. In ovarian cancer, it has been demonstrated that loss of HLA class I antigen on tumor cells correlates with poor outcome, as the interaction of T cells and the HLA receptor is needed to elicit their function (see [122]).…”
Section: Cd24mentioning
confidence: 99%
“…Tumour-associated antigens include cancer-testis antigens, for example, MAGE and ESO; differentiation antigens, such as tyrosinase, which are also expressed in the tissue of origin; oncofetal antigens such as aFP and CEA or overexpressed proteins such as Her2 or wild-type p53 (Antonia et al, 2006;Cloosen et al, 2007;van der Bruggen, 2009;Bioley et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar manner, tumour antigens of the cancer-testis group are largely hidden from developing immune cells. In contrast, most other tumour-associated antigens are expressed in other tissues, including the thymus (Cloosen et al, 2007), resulting in a lymphocyte population that is either deleted or has low affinity for these antigens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation